Das digitale Krankenhaus: Erfordernisse, Handlungsfelder, Umsetzung - Gocke, Peter; Elsner, Christian; Alscher, Alexander; Aulbach, Peter; Baehr, Michael; Beck, Michael; Beivers, Andreas; Dzukowski, Frank (Medizinisch Wissenschaftliche Verlagsgesellschaft, 2023)
Digitalisierung im Krankenhaus gestalten
Literaturangaben
Keywords: Aufsatzsammlung; Digitalisierung; Krankenhaus; Datenschutz; Prozessmanagement